2020
DOI: 10.3390/antibiotics9100667
|View full text |Cite
|
Sign up to set email alerts
|

Promising Antibiofilm Agents: Recent Breakthrough against Biofilm Producing Methicillin-Resistant Staphylococcus aureus

Abstract: Multidrug resistant (MDR) methicillin-resistant Staphylococcus aureus (MRSA) is a superbug pathogen that causes serious diseases. One of the main reasons for the lack of the effectiveness of antibiotic therapy against infections caused by this resistant pathogen is the recalcitrant nature of MRSA biofilms, which results in an increasingly serious situation worldwide. Consequently, the development of innovative biofilm inhibitors is urgently needed to control the biofilm formation by this pathogen. In this work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 56 publications
2
47
1
2
Order By: Relevance
“…Food-borne diseases caused by resistant non-typhoid salmonella are considered important public health threats worldwide [ 24 ]. Several reports tackle the problem of MDR foodborne infections by renewal of the therapeutic options of the medicinal plants [ 25 ] or drug repurposing [ 26 ]. Essential oils extracted from the leaves of Paramignya trimera and Limnocitrus littoralis have antibacterial, antiviral, antimycotic, and antitrichomonas effects [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Food-borne diseases caused by resistant non-typhoid salmonella are considered important public health threats worldwide [ 24 ]. Several reports tackle the problem of MDR foodborne infections by renewal of the therapeutic options of the medicinal plants [ 25 ] or drug repurposing [ 26 ]. Essential oils extracted from the leaves of Paramignya trimera and Limnocitrus littoralis have antibacterial, antiviral, antimycotic, and antitrichomonas effects [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches demonstrated that the SICs of different antimicrobial agents could change the invasion and gene expression of different virulence factors in bacteria, thus leading to minimizing their pathogenicity and virulence [ 15 , 16 , 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the essential oils (EOs) have been gaining considerable interest due to their ability to improve the growth performance, gut health and intestinal integrity, strengthen the mucosal barrier and thereby limit the diseases challenges in poultry 2 4 . Besides, the antibacterial property of EOs has been well recognized 5 , 6 . Thymol, the main phenolic ingredient of thyme ( Thymus vulgaris ) essential oil, is among the reported plant compounds those are used in poultry nutrition as feed additives.…”
Section: Introductionmentioning
confidence: 99%